2008
DOI: 10.1104/pp.107.115279
|View full text |Cite
|
Sign up to set email alerts
|

Genotype, Age, Tissue, and Environment Regulate the Structural Outcome of Glucosinolate Activation    

Abstract: Glucosinolates are the inert storage form of a two-part phytochemical defense system in which the enzyme myrosinase generates an unstable intermediate that rapidly rearranges into the biologically active product. This rearrangement step generates simple nitriles, epithionitriles, or isothiocyanates, depending on the structure of the parent glucosinolate and the presence of proteins that promote specific structural outcomes. Glucosinolate accumulation and myrosinase activity differ by plant age and tissue type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 56 publications
6
83
0
1
Order By: Relevance
“…This ability to modulate the blend may be a response to the fact that each aliphatic GLS is most effective as a defense against a specific set of biotic attackers (Lambrix et al, 2001;Kliebenstein et al, 2002;Kroymann and Mitchell-Olds, 2005;Hansen et al, 2008;Stotz et al, 2011;Züst et al, 2012). Thus, altering the blend may be a way to optimize the defense against a specific set of biotic pests and away from another (Wentzell and Kliebenstein, 2008;Burow et al, 2009). By having a mixture of TFs that directly bypass and TFs that create feed-forward loops with the MYBs, this creates a system in which the plant may be able to precisely finetune the regulation of the biosynthetic genes to optimize the defense of the system using a myriad of inputs including biotic, abiotic, and developmental signals.…”
Section: Signal Integration Can Occur At the Tf And Promoter Levelmentioning
confidence: 99%
“…This ability to modulate the blend may be a response to the fact that each aliphatic GLS is most effective as a defense against a specific set of biotic attackers (Lambrix et al, 2001;Kliebenstein et al, 2002;Kroymann and Mitchell-Olds, 2005;Hansen et al, 2008;Stotz et al, 2011;Züst et al, 2012). Thus, altering the blend may be a way to optimize the defense against a specific set of biotic pests and away from another (Wentzell and Kliebenstein, 2008;Burow et al, 2009). By having a mixture of TFs that directly bypass and TFs that create feed-forward loops with the MYBs, this creates a system in which the plant may be able to precisely finetune the regulation of the biosynthetic genes to optimize the defense of the system using a myriad of inputs including biotic, abiotic, and developmental signals.…”
Section: Signal Integration Can Occur At the Tf And Promoter Levelmentioning
confidence: 99%
“…Surprisingly, research into the effects of plant age on the synthesis of chemicals and its impact on herbivore performance is still scarce (Bowers and Stamp 1993;Campos et al 2003;Wentzell and Kliebenstein 2008;Cartea et al 2009). One previous study of Arabidopsis thaliana revealed that regulation of glucosinolate levels depended on plant age, tissue, and plant density (Wentzell and Kliebenstein 2008), but did not test whether this situation had an impact on insect herbivore performance.…”
Section: Introductionmentioning
confidence: 98%
“…Unfortunately, this effort is complicated by the fact that most phenotypic variation is quantitative and polygenic with at least binary interactions with the environment, development, and second site genetic variation. This variation is further complicated by higher-order interaction among these factors (Falconer and Mackay, 1996;Lynch and Walsh, 1998;Wentzell and Kliebenstein, 2008). Thus, there is a desire to begin identifying the molecular systems controlling these interactions, likely requiring systems biology approaches.…”
Section: Introductionmentioning
confidence: 99%